Teaching English Polysemy through Semantic Fields - Liu, Hsiu-Ying; Kuo, Cheng-Chung; Chou, Yun-Hsuan (Master Program in Linguistics, Diponegoro University, 2019)
The paper aims to explore the effectiveness of Semantic Field Theory in polysemy teaching by conducting action research. The objective is to cultivate students’ concept of metaphor and semantic fields in order to achieve systematic vocabulary retention on the one hand, and to prove that teaching vocabulary through Semantic Field Theory is more effective than traditional methods on the other hand. An experiment is given to sophomores in Asia University, with a pretest, in-class lesson, and posttest. The result shows that the students in the experimental group perform better in the posttest even though their performance in the pretest is worse, which furtherly proves that learning English polysemy through semantic fields is much more effective than traditional teaching methods.